IL-33/ST2 Pathway and Classical Cytokines in End-Stage Heart Failure Patients Submitted to Left Ventricular Assist Device Support: A Paradoxic Role for Inflammatory Mediators?. (10th December 2013) - Caselli, C.; D'Amico, A.; Ragusa, R.; Caruso, R.; Prescimone, T.; Cabiati, M.; Nonini, S.; Marraccini, P.; Del Ry, S.; Trivella, M. G.; Parodi, O.; Giannessi, D.
Abstract : Background . Inflammation is a critical process contributing to heart failure (HF). We hypothesized that IL-33/ST2 pathway, a new mechanism regulated during cardiac stress, may be involved in the functional worsening of end-stage HF patients, candidates for left ventricular assist device (LVAD) implantation, and potentially responsible for their outcome. Methods . IL-33, ST2, and conventional cytokines (IL-6, IL-8, and TNF- α ) were determined in cardiac biopsies and plasma of 22 patients submitted to LVAD implantation (pre-LVAD) and compared with (1) control stable chronic HF patients on medical therapy at the moment of heart transplantation without prior circulatory support (HT); (2) patients supported by LVAD at the moment of LVAD weaning (post-LVAD). Results . Cardiac expression of ST2/IL-33 and cytokines was lower in the pre-LVAD than in the HT group. LVAD determined an increase of inflammatory mediators comparable to levels of the HT group. Only ST2 correlated with outcome indices after LVAD implantation. Conclusions . IL-33/ST2 and traditional cytokines were involved in decline of cardiac function of ESHF patients as well as in hemodynamic recovery induced by LVAD. IL-33/ST2 pathway was also associated to severity of clinical course. Thus, a better understanding of inflammation is the key to achieving more favorable outcome by new specific therapies.